PENGARUH FRAUD DIAMOND TERHADAP FRAUDULENT FINANCIAL REPORTING DENGAN KOMITE AUDIT SEBAGAI VARIABEL MODERASI (STUDI PADA PERUSAHAAN NON CYCLICAL YANG TERDAFTAR.DI BURSA EFEK.INDONESIA.TAHUN 2018-2021) - Tiara Sabhrina; Murtanto Murtanto; Deliza Henny (EBID: Ekonomi Bisnis Digital, 2023)
This research aims to analyze the effects of Fraud Diamond, which is divided into pressure, opportunity, rationalization, and capability, on fraudulent financial reporting with the audit committee as a moderating variable in the consumer goods industry sector in manufacturing corporations listed on the Indonesia Stock Exchange (BEI). In this research, purposive sampling was used to select 24 samples focused on corporations in the non-cyclical consumer goods industry sector during the 2018-2021 period. The data used came from secondary sources, such as financial reports and corporate annual reports downloaded from corporate websites and the Indonesian Stock Exchange website. Data analysis was carried out using a multiple regression model through the SPSS (Statistical Program for Social Science) data processing application. The research results indicate that there is a positive influence of rationalization factors on fraudulent financial reports. However, pressure and opportunity factors do not have a positive influence on fraudulent financial reports. Apart from that, the capability factor has a negative influence on fraudulent financial reports. It is important to note that the audit committee was unable to reduce the influence of pressure, opportunity, capability and rationalization factors on fraudulent financial reports.